CICLO VITAL DE LEPTYSMA ARGENTINA BRUNER 1906 (ACRIDIDAE: LEPTYSMINAE: LEPTYSMINI). VARIABILIDAD EN EL ESQUEMA PRE-REPRODUCTIVO Y REPRODUCCIÓN - Aquino, Ana Lía; Turk, Sonia Z. (Acta Entomológica Chilena, 2022)
Leptysma argentina Bruner 1906 is bivoltine and according to the Ufe span there are few possibilities of generation overlap. The adults lack reproductive diapause. The ovipositional period lasts from 100 to 128 days. The egg laying has a frequency of one egg pod per week. The oviposition is endophytic and in laboratory was achieved in Cyperaceae, Musaceae, Typhaceae and Equisetaceae. An average number of 9 eggs per egg pod was observed. No diapause was registered and the embryo development lasted from 25 to 65 days. The pre-reproductive period involves from 5 to 8 instars. Average duration of the nymphal cycle, according to the number of instars, lasts 95, 131, 179 and 217 days respectively. This variability is present among specimens emerged from the same egg laying and, therefore it could probably be determinated by genetic factors.